The Management of International AcquisitionsThe Management of International Acquisitions, by ChildJohnFaulknerDavid, and PitkethlyRobert. Oxford: Oxford University Press, 2001. - Datta, Deepak K. (Academy of Management Review, 2002)
The article reviews the book ?The Management of International Acquisitions,? by John Child, David Faulkner and Robert Pitkethly.